HUBUNGAN ANEMIA DENGAN DERAJAT DISMENORE PADA MAHASISWI TINGKAT PERTAMA FAKULTAS KEDOKTERAN UNIVERSITAS PATTIMURA TAHUN AKADEMIK 2022/2023 - Pratiwi, Hana Gesti; Tamalsir, Dylan; Riyanti, Novy (Fakultas Kedokteran Universitas Pattimura, 2024)
Dysmenorrhea is menstrual pain that is prone to occur in teenagers, one of which is caused by anemia. Anemia is when the body has low hemoglobin levels, namely <12 g/dl. The function of hemoglobin is to bind oxygen and distribute it throughout the body. If the hemoglobin level is low, myometrial ischemia can occur, and the circulating oxygen level is also low, which can cause myometrial hypoxia, which results in menstrual pain. This study aimed to determine the relationship between anemia and the degree of dysmenorrhea in first-year students at the Faculty of Medicine, Pattimura University, for the academic year 2022-2023. This research is an analytical study with a cross-sectional approach conducted in June 2023, with a sample of 126 female students taken using the simple random sampling method. Measurement of anemia is carried out through examination of hemoglobin levels using the Easy Touch GCHb hemoglobin test tool, and measurement of dysmenorrhea is carried out using the Numeric Rating Scale (NRS) questionnaire. The research results using the Chi-Square statistical test showed no significant relationship between anemia and the degree of dysmenorrhea, with a value of p = 0.885. This research concludes that there is no relationship between anemia and the degree of dysmenorrhea in first-year students at the Faculty of Medicine, Pattimura University, Academic Year 2022-2023.